2021
DOI: 10.1038/s41419-021-03676-x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular fate of intersex differentiation

Abstract: Infertile ovotestis (mixture of ovary and testis) often occurs in intersex individuals under certain pathological and physiological conditions. However, how ovotestis is formed remains largely unknown. Here, we report the first comprehensive single-cell developmental atlas of the model ovotestis. We provide an overview of cell identities and a roadmap of germline, niche, and stem cell development in ovotestis by cell lineage reconstruction and a uniform manifold approximation and projection. We identify common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…Interestingly, we found that two morphologically distinct types of cells similar to fGSCs and SSCs were observed when the GSCs from the ovotestis were cultured. This observation was in line with the recent report showing that common progenitors exist in the intersex gonad [ 17 ]. Based on the single cell RNA-sequencing data, five different subtypes of germline stem cells were identified in ovotestis of M. albus : two common progenitor cell types, early spermatogonia, late spermatogonia, and fGSCs.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Interestingly, we found that two morphologically distinct types of cells similar to fGSCs and SSCs were observed when the GSCs from the ovotestis were cultured. This observation was in line with the recent report showing that common progenitors exist in the intersex gonad [ 17 ]. Based on the single cell RNA-sequencing data, five different subtypes of germline stem cells were identified in ovotestis of M. albus : two common progenitor cell types, early spermatogonia, late spermatogonia, and fGSCs.…”
Section: Discussionsupporting
confidence: 93%
“…Inhibition of BMP signaling results in the premature formation of GSCs [ 50 ]. BMP signaling pathway genes bmp4 , smad7 , and Id1 are abundantly expressed in the Sertoli cells of M. albus , suggesting that somatic-tissue-derived BMP signaling is important for the maintenance of GSCs [ 17 ]. Thus, our data suggested that Wnt and Bmp signaling pathways may play important roles in the maintenance or development of GSCs, which provides key cues for optimizing our GSC medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-cell RNA-sequencing technology has been applied to reveal cellular signatures of ovarian tissue of a few species. So far, the comprehensive ovarian cell atlases were built for humans, 20,21 monkeys, 22,23 drosophilas, [24][25][26] zebrafish, 27 seabass, 28 and finless eel 29 by scRNA-seq. Specific gene signatures of oocyte and granulosa cells were identified at different developmental stages that might reflect both oocyte competency and ovarian reserve in adult human ovaries.…”
Section: Introductionmentioning
confidence: 99%
“…Our data reveal that oocytes are lost via apoptotic cell death during sex change. Histological observations showed that oocytes were decreased in number at the late transition stage (Figure 2e) and these oocytes disappeared in male testes, although a few remaining oocytes were observed in some testes, indicating that oocytes degenerated (Nozu et al, 2013;Wang et al, 2021), indicating that this process is common in protogynous species.…”
Section: Oocyte Disappearance By Apoptotic Cell Deathmentioning
confidence: 99%